Adenovirus-mediated expression of a voltage-gated potassium channel in vitro (rat cardiac myocytes) and in vivo (rat liver). A novel strategy for modifying excitability. - Johns, D C (1995)
Excitability is governed primarily by the complement of ion channels in the cell membrane that shape the contour of the action potential. To modify excitability by gene transfer, we created a recombinant adenovirus designed to overexpress a Drosophila Shaker potassium channel (AdShK). In vitro, a variety of mammalian cell types infected with AdShK demonstrated robust expression of the exogenous channel. Spontaneous action potentials recorded from cardiac myocytes in primary culture were abbreviated compared with noninfected myocytes. Intravascular infusion of AdShK in neonatal rats induced Shaker potassium channel mRNA expression in the liver, and large potassium currents could be recorded from explanted hepatocytes. Thus, recombinant adenovirus technology has been used for in vitro and in vivo gene transfer of ion channel genes designed to modify cellular action potentials. With appropriate targeting, such a strategy may be useful in gene therapy of arrhythmias, seizure disorders, and myotonic muscle diseases.